Gadolinium-doped whitlockite/chitosan composite scaffolds with osteogenic activity for bone defect treatment: In vitro and in vivo evaluations - Xiao, Fei; Shi, Jingjing; Zhang, Xinhai; Hu, Min; Chen, Kangming; Shen, Chao; Chen, Xiaodong; Guo, Yaping; Li, Yang (Frontiers in Bioengineering and Biotechnology, 2023)
Reducing the incidence of bone defects caused by trauma and other primary diseases is an urgent task in modern society. In the present study, we developed a gadolinium-doped whitlockite/chitosan (Gd-WH/CS) scaffold and assessed its biocompatibility, osteoinductivity, and bone regeneration capacity for the treatment of calvarial defect in an Sprague-Dawley (SD) rat model. The Gd-WH/CS scaffolds possessed a macroporous structure, with a pore size ranging 200–300 μm, which facilitated the adhesion of cells and growth of bone tissue into the scaffold. In vitro and in vivo results showed that both the WH/CS and Gd-WH/CS scaffolds were non-cytotoxic to human adipose-derived stromal cells (hADSCs) and bone tissue, which demonstrated the excellent biocompatibility of Gd-WH/CS scaffolds. The Gd3+ ions in the Gd-WH/CS scaffolds significantly improved the osteogenic activity via the GSK3β/β-catenin signaling pathway and upregulated the expression of osteogenic-related genes including osteocalcin (OCN), osterix (OSX), and collagen 1A1 (COL1A1). SD rat cranial defect models further demonstrated that Gd-WH/CS scaffolds significantly accelerated bone tissue growth due to its degradation rate and excellent osteogenic activity. This study suggests the potential utility of the Gd-WH/CS hybrid scaffolds in treating bone defect disease.